Muslim Students, Philanthropic Movements and Political Practice: Narrative Study of The Ikatan Pelajar Al-Washliyah (IPA) in Serdang Bedagai, North Sumatra - Agung Prayogo; Elly Warnisyah Harahap; Muhammad Hidayat (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
This article discusses Muslim student movement is represented of Ikatan Pelajar Al-Washliyah (The Al-Washliyah Student Association) in Serdang Bedagai, North Sumatra. IPA focuses not only on aspects of cadre development and ideological reinforcement in society but is also actively involved in all societal developments, including politics. The narrative study raises the question of how the political movement played of IPA. The research findings explain in political activity starts from the philanthropic movement based in the community, i.e. raising funds and distributionto help the welfare of the society. Then, the new direction of IPA activities has been towards the political practice, whether done openly or privately with provide open support and call for the election of a particular regional head candidate.